Validity and reliability of the English version of the Diabetic Foot Self-Care Questionnaire: a cross-cultural adaptation - María Ruiz-Muñoz; Raúl Fernández-Torres; Cynthia Formosa; Alfred Gatt; Gabriel Gijón-Noguerón; Emmanuel Navarro-Flores; Manuel González-Sánchez (Frontiers Media S.A., 2024)
IntroductionThe objective of this study was to carry out the cross-cultural adaptation and validation of the Diabetic Foot Self-Care Questionnaire into the English language, broadening the applicability of this patient-reported outcome measure and improving the monitoring of patients with diabetic foot disease.MethodsThe validation study into English was conducted in two phases: cross-cultural adaptation and psychometric validation study. Short Form-12 Version 2, EuroQoL-5D and Foot Function Index were used to analyze the criterion validity. Item response, internal consistency, standard error of measurement, minimal detectable change and construct validity were calculated in the validation phase.ResultsAn English version of the questionnaire (DFSQ-UMA-En) was successfully obtained. A total of n = 193 participants were tested to confirm the validity and reliability of the questionnaire. Internal consistency values ranged from very good to excellent (Cronbach's α =0.889-0.981), and reliability was excellent (ICC = 0.854-0.959). Standard error measurement value was =2.543. Criterion validity ranged from r = 0.429 to r = 0.844. For construct validity, Kaiser-Meyer-Olkin test was =0.752.ConclusionDFSQ-UMA-En is a valid and reliable tool with good readability and comprehension features. This questionnaire addresses foot self-care behaviors in patients with diabetic foot disease, standing out as essential for early diagnosis and prevention strategies in clinical and research settings.